2017
DOI: 10.22159/ijpps.2017v9i2.15511
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Biological Screening of Aminoacetylenic Tetrahydrophthalimide Analogues as Novel Cyclooxygenase (Cox) Inhibitors

Abstract: Objective: To design and synthesise a new amino acetylenic tetrahydro phthalimide derivative and investigate their selective inhibitory activity to COXs. Methods:Aminoacetylenic tetrahydro phthalimide derivatives were synthesised by alkylation of tetrahydro phthalimide with propargyl bromide afforded 2-(prop-2-yn-1-yl)-2,3,3a,4,7,7a-hexahydro-1H-isoindole-1,3-dione. The alkylated tetrahydro phthalimide was subjected to Mannich reaction afforded the desired amino acetylenic tetra phthalimide derivatives (AZ 1-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…19 The Aryl group that could selectively differentiate between COX-1 and COX-2 inhibitory activity of aminoacetylenic analogues. 10,11,12 in our study we suggest that the removal of the acetylenic group in this study showed that it might be a different binding site in COXs which may result in effective compounds. there is no precise or specific pattern observed at COXs binding sites 23…”
Section: Chemistrymentioning
confidence: 59%
“…19 The Aryl group that could selectively differentiate between COX-1 and COX-2 inhibitory activity of aminoacetylenic analogues. 10,11,12 in our study we suggest that the removal of the acetylenic group in this study showed that it might be a different binding site in COXs which may result in effective compounds. there is no precise or specific pattern observed at COXs binding sites 23…”
Section: Chemistrymentioning
confidence: 59%
“…19 The Aryl group that could selectively differentiate between COX-1 and COX-2 inhibitory activity of aminoacetylenic analogues. 10,11,12 in our study we suggest that the removal of the acetylenic group in this study showed that it might be a different binding site in COXs which may result in effective compounds. there is no precise or specific pattern observed at COXs binding sites 23…”
Section: Chemistrymentioning
confidence: 59%
“…9 As a part of our investigation for the structure relationship activity (SAR) for amino acetylenic isoindoline-1,3-dione as anti-inflammatory agent, in this paper; the acetylenic moiety was removed to generate isoindoline-1,3-dione derivatives of potential COXs inhibitors. 10,11,12 11 A mixture of Formaldehyde (39%, 30.1 mL), Heterocyclic amine e.g. 2,6 dimethylpiperidine (1.7 g, 0.01 mole) and 50ml ethanol was heated and stirred under reflux for 30 minutes at a temperature of 70ᵒC.…”
Section: Introductionmentioning
confidence: 99%